Analisis Pelaksanaan Model Discovery Learning Serta Pengaruhnya Terhadap Sikap Kreatif Dalam Pembelajaran Kelarutan Di Kelas XI MIA SMAN 2 Kota Jambi - Jufri, Siti Fatimah; Srimadona, Agus (Integrated Science Education Journal, 2022)
Research Objectives: This study aims to determine the extent of the implementation of the discovery learning model and its effect on the creative attitudes of students in learning the material solubility and solubility product (Ksp) in class XI MIA SMAN 2 Jambi City. Methodology: This study is an associative descriptive study with a Pre-Experimental Design type of One-Shot Case Study. Data is collected by means of a concurrent embedded mix method. The sampling technique was carried out using the purposive sampling technique. The research instrument was an observation sheet on the implementation of the discovery learning model from both teachers and students as well as an observation sheet and a questionnaire on the creative attitude of students. Main findings: The results of the study indicate that there is a relationship between the implementation of the discovery learning model and the creative attitude which is categorized as strong with an average rxy of 0.633 and there is also an effect of the implementation of the discovery learning model on the creative attitude of students. Research update: Thus, it can be concluded that the discovery learning model in the learning of solubility and solubility product (Ksp) in class XI 5 MIA SMAN 2 Jambi City has been implemented well so that students can develop a creative attitude in the learning process. Besides, the implementation of the discovery learning model can improve the creative attitude of students in the learning process.